STUDENTS’ CHARACTER INTERNALIZATION MODEL OF HONESTY MI MIFTAHUL ULUM BATU CITYEAST JAVA - Janah, Roikhatul (As-Sibyan, 2019)
This study is triggered by the increasing number of honest people, there have been many cases of one’s dishonesty that occur among governmental officers, community leaders, until elementary schools students. These facts are real problems that must be examined and must be solved. This study employs qualitative approach with focuses on how the strategies and steps of students honest character internalization in MI Miftahul Ulum Batu City, East Java. The based on research focus, the students honest character internalization model in MI Miftahul Ulum Batu City, East Java is structural organic rational development model.